Intravascular Leiomyoma Considered Preoperatively as Uterine Sarcoma: A Rare Case - Yingyao Wang; Song Xu; Caibo Wang; Wenjuan Li; Jianhao Xu; Zhiwei Zhu; Qin Liu; Lixia Zhu (Women's Health Reports)
Intravascular leiomyoma (IVL) is usually defined as a histologically benign leiomyoma that originates in a uterine fibroid or the intrauterine vein wall and grows and expands intravenously. We report a case in which pelvic IVL was detected early and discuss the early diagnosis of and best treatment for this tumor.